Lab-on-Chip-Based Platform for Fast Molecular Diagnosis of Multidrug-Resistant Tuberculosis - Cabibbe,AM; Miotto,P; Moure,R; Alcaide,F; Feuerriegel,S; Pozzi,G; Nikolayevskyy,V; Drobniewski,F; Niemann,S; Reither,K; Cirillo,DM (Journal of Clinical Microbiology, 2015)
We evaluated the performance of the molecular lab-on-chip-based VerePLEX Biosystem for detection of multidrug-resistanttuberculosis (MDR-TB), obtaining a diagnostic accuracy of more than 97.8% compared to sequencing and MTBDRplus assay forMycobacterium tuberculosis complex and rifampin and isoniazid resistance detection on clinical isolates and smear-positivespecimens. The speed, user-friendly interface, and versatility make it suitable for routine laboratory use.